Pengaruh Motivasi dan Kompensasi Finansial Terhadap Loyalitas Karyawan PT Rheino Putra Gemilang - Krispravia Caesariano; Windayanti (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine whether there is an influence between work motivation and financial compensation on employee loyalty. This study uses a quantitative approach through a survey of 43 employees. The entire population is made until. The results of the hypothesis test (t test) which shows that the motivation variable has a significant effect on employee loyalty is shown by t count of 2,294 which is greater than t table. But the compensation variable has no significant effect with t count of 1.084 which is smaller than t table. The conclusion of this study is that motivation is the most dominant variable on employee loyalty. This can be interpreted that employee loyalty is seen from the way the company provides motivation to employees